Unit Labor Cost Growth Differentials in the Euro Area, Germany, and the US: Lessons from PANIC and Cluster Analysis - Ulrich Fritsche; Vladimir N. Kuzin (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Inflation differentials in the Euro area are mainly due to a sustained divergence of wage developments across the Euro area, and narrower differences in labour productivity growth (Alvarez et al., 2006). We investigate convergence of inflation using unit labour cost (ULC) growth and applying PANIC (Bai and Ng, 2004) and cluster procedures (Hobijn and Franses, 2000, Busetti et al., 2006) to Euro area countries as well as US States, US Census Regions and German Länder. Euro area differs in that dispersion in general (and its fraction due to idiosyncratic factors in specific) is larger and common factors are much less important in explaining the variance of ULC growth. We report evidence for convergence clusters in all countries.
Keywords: E31; O47; C32; C33; 330; Unit labor costs; inflation; European Monetary Union; Germany; United States of America; convergence; convergence clubs; panel unit root tests; Inflationskonvergenz; Inflationsrate; Lohnstückkosten; Arbeitsproduktivität; Entwicklungskonvergenz; Schätzung; Europäische Wirtschafts- und Währungsunion; EU-Staaten